Cu-Sn-S plasmonic semiconductor nanocrystals for ultrafast photonics. Issue 43 (20th October 2016) - Guo, Qiangbing; Ji, Meixi; Yao, Yunhua; Liu, Meng; Luo, Zhi-Chao; Zhang, Shian; Liu, Xiaofeng; Qiu, Jianrong
Abstract : Novel saturable absorber based plasmonic semiconductor nanocrystals for fs pulse generation at the telecommunication band. Abstract : Here, we show that solution-processed Cu-Sn-S semiconductor nanocrystals (NCs) demonstrate a tunable localized surface plasmon resonance band in the near infrared region, where strong saturable absorption occurs. A saturable absorber based on these plasmonic NCs enables the construction of a stable mode-locked femtosecond fiber laser operating at the telecommunication band.